(3CUd UfGYI GdCMcGe GdadcjIs - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s
(3ChdgG (B:s
(3bGd Efi LeYJ ai gPG GdcJGH ef CUd UfGYI GdCMcGe hLedgG , hGdWQjb Edi GdJUQa ajgG hESJYeGdgG eG XffJg cGajkG ai eYfGg s
(3BNQgG (B:s
(3hdG JYLd HGdMce EdG HYO GdacQ GdcKjQ , hGdfXQ GdWhjd , hGdJCed GdTGai hfNJe GdebGdI GdQGHYI HgPG GdHGH , hGdcJGH HgPg GdebGdI hGdMeO ddg s
(3HgG LOGhds
(3HBNQgG (B_ (3ai fMh SHY hQbGJ (B_ (3LOGhd hTQhMs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B838s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B252 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B397 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs